Exploring Motivated Participation in Spoken English Learning among Tertiary English Majors - Zhenzhen Ma; Chili Li (Universitas Sebelas Maret, 2025)
This study investigated the motivated participation in spoken English learning among 148 Chinese tertiary English majors through a questionnaire survey grounded in Dörnyei’s L2 Motivational Self System framework. Descriptive statistics revealed two key dimensions of motivation: 1) the oral motivated self system, where participants demonstrated a high level of Ideal Oral Self, Group, and Peer, alongside a medium level of Ought-to Oral Self, Oral Learning Experience, and Class; and 2) motivated classroom participation, marked by a high level of Group and Peer and a medium level of Class. Independent samples t-tests identified no significant differences across six motivational factors between freshmen-sophomores or sophomores-juniors, but freshmen exhibited significantly stronger Class Environment engagement than juniors, indicating a decline in structured classroom motivation with academic progression. These findings emphasize the centrality of peer collaboration and ideal self-imagery in sustaining motivation while advocating for curriculum reforms to address declining classroom engagement in advanced cohorts. The study provides actionable insights for educators to design peer-driven activities and adaptive pedagogical strategies, ultimately enhancing oral proficiency and overall language competence among English majors.